Survive the economic downturn: Operating flexibility, productivity, and stock crash - Li, Yang; Wang, Xiaojun; Xu, Fangming; Ho, Tuan (Journal of Operations Management, 2025)
Abstract Operating flexibility supports a firm's resilience strategy during challenging times by enabling them to promptly cut down operating costs associated with unproductive resources. We employ a real options model to formalize this insight. Our empirically grounding analytics motivate a firm‐level proxy for downscale operating flexibility (FLEX), which effectively captures the adjustment frictions across different contexts of firms' operations. Using U.S. data between 1961 and 2020, we show that operating flexibility mitigates the risk of stock price crashes, especially during periods of economic recession. Consistent with the loss‐curtailment mechanism, the operating flexibility effect is more pronounced for firms with lower productivity/profitability or higher operating leverage and is further amplified during longer and more severe recessions. Managers may avail themselves of our well‐tested empirical measure of operating flexibility to guide their efforts in building a more resilient operations structure.